Papa, maman : noms propres ou noms de parenté ordinaires ? - Mathilde Salles (Discours)
This paper is devoted to some uses of papa [dad], maman [mom] without a determiner, some naked uses in which they refer to a third person’s father or mother, like a possessive anaphoric phrase such as his father or his dad, or to a member of a family, like an associative anaphoric phrase such as the father or the dad. The first case is illustrated by an example like Qu’il se soit payé l’ancien appartement de Claude Zidi, soit… Papa est richissime, mais qu’il ne paye pas d’impôt!!!!, in which one could easily replace papa with son père [his father]; the second by an example like Pas loin dans une clairière, y a une famille qui casse la croûte, avec table et pliants… Papa, maman et la grande fille…, in which one could replace papa, maman, with le père, la mère [the father, the mother]. Our comparisons suggest that papa, maman are anaphoric in these kinds of uses. But is it really the case? And, in conjunction with the preceding question, are papa, maman ordinary kinship nouns here, comparable to those which enter into the formation of anaphoric nominal phrases as his father, his dad, the father, the dad? We will try to answer these questions, starting with studying the characteristics of the naked uses of papa, maman in some forms of reported speech. We can then point out that papa, maman are mainly proper names, not only in their ordinary situational uses (i.e. their uses as address terms and uses in which they refer to the speaker’s or interlocutor’s father or mother), but also in other naked uses.